FUTURE TRENDS OF RED MEAT PRODUCTION IN PAKISTAN: TIME SERIES ANALYSIS - M. N. Akram; M. Amin; A. Yasin; M. Z. Aslam (Journal of Animal and Plant Sciences, 2022)
Meat specifically red meat is an important source of high-quality proteins, fibre, iron and vitamins in the diet of people. The demand of meat and meat products is rising day by day due to the rapid population growth. But the traditional system is not able to meet this growing demand and it is necessary to tackle the upcoming situations. Production of red meat may fluctuate due to droughts, Foot-and-Mouth Disease Virus (FMDV) and an early age of slaughtering. For this, forecasting is the main tool which is used to determine the production of red meat in coming years. In this study, we use time series data from 1996-2019 to forecast next six years for red meat production of Pakistan. Different time series models are fitted to select the most suitable one. Results concluded that the random walk model with drift is the most suitable model because of minimum AIC and SBIC values. This model is further used for forecasting purposes for the time periods 2020-25. Red meat production of Pakistan may expect to be increasing 15.81% in 2025 as compared to 2019.
Keywords: AIC; Forecasting; Production; Red meat and Time series models